Identification of the silkworm quail gene reveals a crucial role of a receptor guanylyl cyclase in larval pigmentation. (January 2016) - Yuasa, Masashi; Kiuchi, Takashi; Banno, Yutaka; Katsuma, Susumu; Shimada, Toru
Abstract: Diverse color patterns on the integument of lepidopteran larvae play important roles in their survival through camouflage, mimicry, sexual signaling, and aposematism. In the silkworm Bombyx mori, many color pattern variations have been preserved in inbred strains making them a good model for elucidating the molecular mechanisms that underlie color pattern formation. In this study, we focused on the silkworm quail ( q ) mutant, which exhibits abnormalities in multiple pigment biosynthesis pathways. Positional cloning of the q gene revealed that disruption of a guanylyl cyclase gene, BmGC-I, is responsible for its abnormal pigmentation. In q mutants, we identified a 16-bp deletion in the BmGC-I transcript, resulting in the production of a premature stop codon. Knockout of the BmGC-I gene resulted in the q -like abnormal pigmentation, thereby demonstrating that the BmGC-I gene is involved in the pigment biosynthesis pathway in the integument. Moreover, quantitative reverse transcription polymerase chain reaction showed that BmGC-I was strongly expressed in the fourth instar on day 2. Our results suggest that BmGC-I deficiency affects the pigment biosynthesis pathway, which supports the involvement of guanylyl cyclase in larval coloration. Graphical abstract: Highlights: The silkworm quail mutant shows extra black spots and pinkish color on larval skin. Positional cloning identified a gene responsible for quail . The responsible gene encodes a guanylyl cyclase protein, BmGC-I. Knockout of BmGC-I causes the quail -like pigmentation pattern.